Clustering Pada Pelanggan Perusahaan Air Bersih Dengan Algoritma K-Means - Arif Ramadhan Siregar; Sundari Retno Andani; Widodo Saputra (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2019)
progress, and increasing living standards have caused the need for clean Clean water services are a very important component of public services. Water is a basic need that cannot be separated from human life. The supply of clean water is of particular concern to every country in the world, including in Indonesia. Population growth, development water to continue to increase. Technological improvements and rapid population growth are now encouraging mineral water companies to continue to innovate and expand their market network in order to continue to survive and compete with companies - companies. A product that can be desired by consumers must be able to provide satisfaction to consumers who consume these products. In realizing the goals to achieve customer satisfaction, companies must be able to learn in advance about products that consumers are interested in, habits carried out by consumers, why consumers are interested in consuming these items, and how many products are needed by consumers. The author wants clean water customers which will be clustered using the K-means algorithm to do which provinces will get customers of clean water companies.